Historyographical Analysis of the Investigation State of the Discussions about the Ancient Languages Teaching in the Gymnasiums (Late XIX Early XX Century) - Alla Paladieva (Pedagogical Discourse, 2013)
The article deals with the  investigation state of the problem and it has been revealed that the discussions about teaching of ancient languages in gymnasiums in late XIX and early XX century included different views concerning the projects of the regulations of secondary educational establishments; reformation of the secondary education, the development of the gymnasium education; the teaching of Greece and Latin languages in the classical and real gymnasiums; advantages and disadvantages of classicism and realism; positions of the defenders and opponents of the teaching of ancient languages; improvement of the educational and up-bringing process; pupils’ overstrain and low level of their general development; bad state of the quality of the given knowledge; different types of secondary school; forming of united educational establishment.